2015
DOI: 10.1016/j.jgeb.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B polymorphism distribution among a sample of obese Egyptian females with visceral obesity and its influence on lipid profile

Abstract: BackgroundRegional distribution of adipose tissue is more important than total amount of body fat in predicting complications associated with obesity. Apolipoprotein B (Apo B) plays a central role in lipid metabolism.AimTo investigate the importance of the XbaI polymorphism of Apo B gene (C7673T) as risk factor for visceral obesity and its influence on lipid profile.Subjects and methodsTotal of 122 obese adult females (BMI ⩾ 30 kg/m2): 56 of them with visceral obesity (⩾7 cm by abdominal Ultrasound) and 66 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Therefore, the interactions between APOA1 rs670 and obesity might contribute to low HDL-C diseases, and might increase the risk of low HDL-C diseases. The results are in line with some previous studies [ 30 , 50 – 52 ] which supports the association between ApoA1 gene, obesity and serum HDL-C levels.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the interactions between APOA1 rs670 and obesity might contribute to low HDL-C diseases, and might increase the risk of low HDL-C diseases. The results are in line with some previous studies [ 30 , 50 – 52 ] which supports the association between ApoA1 gene, obesity and serum HDL-C levels.…”
Section: Discussionsupporting
confidence: 93%
“…A higher prevalence of atherosclerotic plaques in carotid arteries of T homozygotes has also been reported (13). Some studies have also found association of this polymorphism with CVD, increased apoB, TC, TG, and LDL levels, and decreased HDL levels (5,(14)(15)(16)(17). On the other hand, some studies found no association between these parameters (9,11,18).…”
Section: Introductionmentioning
confidence: 95%
“…The literature consistently reassures the association between dyslipidemia and incidence of vascular events, with strong etiological contribution by increased triglyceride (TG), low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), and apolipoprotein B (apoB) levels, as well as by reduction of high-density lipoprotein (HDL) levels (4,5). With subendothelial retention of apolipoprotein(apo)B-containing particles as a necessary trigger for atherogenesis, levels of this apolipoprotein present predictive power for vascular events as high as those of LDL (6,7).…”
Section: Introductionmentioning
confidence: 99%
“… 28 Apo B mutations may favor liver absorption of dietary fats or VLDL secretion. 29 Apo B mutations also result in altered association with capillary lipoprotein lipase, which favors triglyceride hydrolysis and fat deposition. Some previous studies have found that Apo B levels are stronger risk factors for obesity than LDL.…”
Section: Discussionmentioning
confidence: 99%